2015
DOI: 10.1109/tmtt.2015.2428242
|View full text |Cite
|
Sign up to set email alerts
|

Design of Compact Reflection-Type Phase Shifters With High Figure-of-Merit

Abstract: This paper presents reflection-type phase shifters (RTPSs) with very high figure-of-merit (FoM) and low insertion-loss variation, achieving up to 360 relative phase shifts. Two compact topologies are proposed. They were implemented at the working frequency of 2 GHz on a printed circuit board technology. The reflection loads are based on the use of one transmission line loaded by varactors, forming L-or -type networks. An automatic procedure is given to design the electrical length and the characteristic impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…In References 4 and 5, a high phase shift range (PSR) has been achieved by modifying a hybrid coupler arm and reflection load; however, IBPD error is high. Similarly, the tunable phase shifter is designed by controlling coupling coefficient of coupled with varactor diode .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…In References 4 and 5, a high phase shift range (PSR) has been achieved by modifying a hybrid coupler arm and reflection load; however, IBPD error is high. Similarly, the tunable phase shifter is designed by controlling coupling coefficient of coupled with varactor diode .…”
Section: Introductionmentioning
confidence: 98%
“…In Reference , the coupled line where varactor was connected at the center point achieved 360° PSR; however, IBPD error is higher than ±20°. From the literature reviews, it can be concluded that conventional RTPS has drawbacks such as limited BW in terms of IBPD error and insertion loss (IL) variations …”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations